Next generation sequencing based genotyping, cytometry and phenotyping for understanding diversity and evolution of guinea yams - Girma, G.; Hyma, K.E.; Asiedu, Robert; Mitchell, S.E.; Gedil, Melaku A; Spillane, Charles (Springer, 2014)
Key message Genotyping by sequencing (GBS) is used to understand the origin and domestication of guinea yams, including the contribution of wild relatives and polyploidy events to the cultivated guinea yams. Abstract Patterns of genetic diversity within and between two cultivated guinea yams (Dioscorea rotundata and D. cayenensis) and five wild relatives (D. praehensilis, D. mangenotiana, D. abyssinica, D. togoensis and D. burkilliana) were investigated using next-generation sequencing (genotyping by sequencing, GBS). Additionally, the two cultivated species were assessed for intra-specific morphological and ploidy variation. In guinea yams, ploidy level is correlated with species identity. Using flow cytometry a single ploidy level was inferred across D. cayenensis (3x, N = 21), D. praehensilis (2x, N = 7), and D. mangenotiana (3x, N = 5) accessions, whereas both diploid and triploid (or aneuploid) accessions were present in D. rotundata (N = 11 and N = 32, respectively). Multi-dimensional scaling and maximum parsimony analyses of 2,215 SNPs revealed that wild guinea yam populations form discrete genetic groupings according to species. D. togoensis and D. burkilliana were most distant from the two cultivated yam species, whereas D. abyssinica, D. mangenotiana, and D. praehensilis were closest to cultivated yams. In contrast, cultivated species were genetically less clearly defined at the intra-specific level. While D. cayenensis formed a single genetic group, D. rotundata comprised three separate groups consisting of; (1) a set of diploid individuals genetically similar to D. praehensilis, (2) a set of diploid individuals genetically similar to D. cayenensis, and (3) a set of triploid individuals. The current study demonstrates the utility of GBS for assessing yam genomic diversity. Combined with morphological and biological data, GBS provides a powerful tool for testing hypotheses regarding the evolution, domestication and breeding of guinea yams.